THE EFFECT OF JOB SATISFACTION, WORK DISCIPLINE, AND ORGANIZATIONAL COMMITMENT ON EMPLOYEE PERFORMANCE - Ni Putu Seftiana Dewi; Nengah Landra; Gde Bayu Surya Parwita (EMAS: Jurnal Ekonomi, Manajemen dan Bisnis, 2025)
Achieving optimal employee performance in achieving organizational goals is the main objective of human resource management. The Dauh Puri Kaja Village Office is the location of this study. Thirty-five employees from the Dauh Puri Kaja Village Office constitute the study population. Due to the relatively small study population, the census method was chosen. Thirty-five employees of the Dauh Puri Kaja Village Office constitute the study sample. Questionnaires and Likert scale interviews were the methods used to collect data. Instrument validation, including validity and reliability testing, was the initial step in data analysis. Multiple Linear Regression Analysis was the subsequent step. The results of this study indicate that Job Satisfaction, Work Discipline, and Organizational Commitment have a positive and significant impact on Performance among employees at the Dauh Puri Kaja Village Office.